Student evaluation of the impact of changes in teaching style on their learning: a mixed method longitudinal study - Susan Jones; Somasundari Gopalakrishnan; Charles A. Ameh; Brian Faragher; Betty Sam; Roderick R. Labicane; Hossinatu Kanu; Fatmata Dabo; Makally Mansary; Rugiatu Kanu; Nynke van den Broek (BMC Nursing, 2018)
Abstract Background Maternal and Child Health Aides are the largest nursing cadre in Sierra Leone providing maternal and child health care at primary level. Poor healthcare infrastructure and persistent shortage of suitably qualified health care workers have contributed to high maternal and newborn morbidity and mortality. In 2012, 50% of the MCHAides cohort failed their final examination and the Government of Sierra Leone expressed concerns about the quality of teaching within the programmes. Lack of teaching resources and poor standards of teaching led to high failure rates in final examinations reducing the number of newly qualified nurses available for deployment. Methods A mixed-methods approach using semi-structured observations of teaching sessions and completion of a questionnaire by students was used. Fourteen MCHAide Training Schools across all districts of Sierra Leone, 140 MCHAide tutors and 513 students were included in the study. In each school, teaching was observed by two researchers at baseline, 3 and 6 months after the tutor training programme. Students completed a questionnaire on the quality of teaching and learning in their school at the same time points. Results A total of 513 students completed the questionnaire, 120 tutors took part in the training and 66 lessons across all schools were observed. There was a statistically significant (p < 0.05) improvement in mean student evaluation of teaching and learning in 12/19 areas tested at follow-up compared to baseline. Observation of 66 teaching sessions demonstrated an increase in the number of student-focused, interactive teaching methods used. Conclusion Prior to the teaching and learning workshops there was little student-focused learning within the schools. Teaching was conducted predominantly using lectures even for practical sessions. Training tutors to move away from didactic teaching towards a more student-focused approach leads to increased student satisfaction with teaching and learning within the schools.